2018
DOI: 10.1002/art.40413
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of Tumor Necrosis Factor Receptor II Induces Antiinflammatory Responses and Alleviates Experimental Arthritis

Abstract: Our findings support the use of TNFRII-selective therapeutics as an effective approach to the treatment of arthritic disease and possibly other inflammatory and autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 52 publications
4
41
0
Order By: Relevance
“…The relevance of TNFRII signaling on Treg cells was shown in other experimental models. In graft‐versus‐host disease, a blocking antibody against TNFRII abolished the disease control exerted by Treg cells , whereas TNFRII agonists could protect against graft‐versus‐host disease and ameliorate CIA by promoting Treg cell expansion . TNFRII expression in other immunomodulatory cells, such as myeloid‐derived suppressor cells (MDSCs), could also be associated with protection against inflammation, because TNFRII −/− mouse MDSCs are less suppressive .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of TNFRII signaling on Treg cells was shown in other experimental models. In graft‐versus‐host disease, a blocking antibody against TNFRII abolished the disease control exerted by Treg cells , whereas TNFRII agonists could protect against graft‐versus‐host disease and ameliorate CIA by promoting Treg cell expansion . TNFRII expression in other immunomodulatory cells, such as myeloid‐derived suppressor cells (MDSCs), could also be associated with protection against inflammation, because TNFRII −/− mouse MDSCs are less suppressive .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the proinflammatory effects of TNF are generally considered to be mediated by TNFRI , whereas the immunosuppressive effects of TNF are considered to be mediated by TNFRII . In particular, the antiinflammatory effects of TNF may be dependent on its ability to activate and expand TNFRII‐expressing Treg cells .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, expression of TNFR2 defines a maximally suppressive subset of mouse Tregs (Chen et al, 2008), indicating that TNFR2 activation regulates suppressive activity of Tregs. Indeed, it was shown that exogenous activation of TNFR2 leads to expansion of Tregs, alleviates arthritic disease and protects from acute graft versus host disease (Chopra et al, 2016;Fischer et al, 2018;Lamontain et al, 2018). Our published data indicate that presence of IL-2 dramatically increases TNFR2-dependent Treg expansion in vitro (Fischer et al, 2017;Fischer et al, 2018).…”
Section: Introductionmentioning
confidence: 64%
“…Indeed, it was shown that exogenous activation of TNFR2 leads to expansion of Tregs, alleviates arthritic disease and protects from acute graft versus host disease (Chopra et al, 2016;Fischer et al, 2018;Lamontain et al, 2018). Our published data indicate that presence of IL-2 dramatically increases TNFR2-dependent Treg expansion in vitro (Fischer et al, 2017;Fischer et al, 2018). Because of the apparent requirement of a combined activation of IL-2 and TNFR2 signal pathways we have developed a novel, dualacting cytokine fusion protein, where IL-2 is fused by genetic engineering to a TNFR2-selective TNF mutein.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of TNFR2 activation in a murine model of arthritis with EHD2‐sc‐mTNFR2 was reported. TNFR2 activation in mice with CIA resulted in the expansion of Treg cells and in a decrease of clinical symptoms 170 . Specifically, administration of TNFR2 agonist EHD2‐sc‐mTNFR2 before clinical symptoms led to delayed EAE disease onset with decreased clinical scores, mechanical allodynia, and T cell infiltration in CNS, 171 whereas therapeutic administration of TNFR2 agonist EHD2‐sc‐mTNFR2 resulted in disease amelioration, expansion Treg cells, and decreased demyelination 171 …”
Section: Introductionmentioning
confidence: 99%